مصادر الضغوط النفسية و أثرها في تفعيل التدريس المقاربة بالكفاءات لدى أساتذة التربية البدنية و الرياضية للتعليم المتوسط - لحول, أبو بكر; شوقي, بدرة (Institut d’Éducation Physique et Sportive/Université de Mostaganem 2013/2014, 2014)
The conclusion of the study :Title of study The sources of spychologecal streesing and it effecting on activation of pedagogical comption at the teach of physical education sportive in midlle emeignent secondary school allthough there is relaten ship between study pedagogical competition and psgchological stressing and its effected on the nature of relatneshipe learner/teacher and according to this we are the researchers students try to take a look on this object in the new methology which seems to has many goals : Knowing the sources of psychological stressing the teachers of physicals education and sportive Knowing if the teachers have the ability to deals with the method by education of pedagogicale competition Knowing the relationship between psychological stressing and education hypotheses of reaserch we check it like this There is relatoinship between psychological stressing and education pedagogicale competition for the teachers of physical educcation and sportive in secondary school For check this puthese and the rest we use theoncal approach on 40 sangels from teachers which choried from the orginal society which is the teachers of physical education and sportive of secondary school of tiaret and mostaganem and we discaset this research on two parts : The first chapter concen in theorical study and the second chapter we make it to the champing study in ride it we selected the research tools which selected in quation and scientific bases for testing from realist and objective then principle study then the way that use it and the teachers and after the traitement statistic we show the results which mean that these is relatneship between two variables of psychological stressing and the education competition what ever the education psychological rise up the strees get down For this we get out the next recommendation : 1- sensbilize the teachears of education physecal and sporive to take attention of the phono,on of stressing 2-how the teachers walk with the new method in edycation 3-try to do a turn of wising and contuned psychological value to psychological stressing of physical education 4- keys words pedagogical comgpetition psychological stressing teachers of physical education and sportive in the secodany school
MEPS-2013-2014-88
Keywords: الضغوط النفسية - تفعيل التدريس - المقاربة بالكفاءات - أساتذة التربية البدنية و الرياضية - للتعليم المتوسط